SPECIFIC FEATURES OF FIELDS OF STRESSES ASSOCIATED WITH AFTERSHOCK PROCESSES IN THE ALTAI-SAYAN MOUNTAINOUS REGION - Olga A. Kuchay (Геодинамика и тектонофизика, 2015)
The cataclastic method developed by Yu.L. Rebetsky is applied to reconstruct the recent field of stresses related to aftershock sequences of earthquakes that occurred in the Altai-Sayan mountainous region, specifically the Altai earthquake of 27 September 2003 (М=7.3; φ=50.061o; λ=87.966o) and the Busingol earthquake of 27 December 1991 (М=5.0; φ=51.1o; λ=98.13o). Upon reconstruction of the field of stresses from data on aftershocks of different magnitudes, it is revealed that orientations of maximum stresses are misaligned, and this may suggest a lack of similarity of fields of stresses in different scale ranks. The fields of stresses reconstructed from data on sequences of weak aftershocks of the Altai and Busingol earthquakes show changes in orientations of major stress axes at opposite sides of the shear faults under study. The orientation of the maximum deviation stress axes due to strong aftershocks is consistent with the regional field of stresses and does not change in the vicinity of the fault plane associated with the strong earthquakes the Altai and Sayan regions.